(untitled) (GIST – Education and Learning Research Journal, 2014)
The present study reports the results of a process of peer feedback through anonymous peer review in an EFL writing class. Numerous studies have reported on the benefits of peer review (PR) in the ESL/EFL writing classroom. However, the literature also identifies social issues that can negatively affect the outcome of face-to-face PR. In this study, twenty-five students were enrolled in an expository writing class in an Intensive English Program (IEP) of a private, American university in Madrid, Spain, where they attended 25 contact hours of English per week and experienced anonymous, or blind, peer review (PR). It was hoped that removing social interferences would force the participants to focus on the type and number of corrections they made to an unknown classmate’s essay and as well as increase the type and number of corrections s/he incorporates into her/his original essay. Results indicate that writers accepted most of the changes proposed by the PR process (70%), an acceptance rate unprecedented in other studies.